A morphological and cytogenetic study of two Fulakora Mann, 1919 (Hymenoptera: Formicidae), with the description of a new species - Jacintho, Gabriela De Figueiredo; Chaul, Júlio Cezar Mário; Teixeira, Gisele Amaro; Barros, Luísa Antônia Campos; Lopes, Denilce Meneses; Serrão, José Eduardo (Zootaxa, 2025)
The Amblyoponinae genus Fulakora comprises 25 Neotropical, Nearctic and Australasian species. To date, only one species of Fulakora, F. cleae, has been cytogenetically studied, with 2n=18 chromosomes, and no information is available on the immature stages of the genus. In this study, we describe two additional karyotypes for Fulakora (F. elongata and a new species), both with 2n=24 chromosomes (16 metacentrics + 8 submetacentrics), which differ from the previously reported karyotype for the genus. We describe the new species, Fulakora estevae sp. nov., and compared it to the most similar species of the genus. The larval stages of F. estevae sp. nov. and of F. elongata are described and compared. Finally, we provide a key to all Neotropical Fulakora species.